2020
DOI: 10.1002/col.22480
|View full text |Cite
|
Sign up to set email alerts
|

The impact of signboard‐building color combinations on color harmony and legibility

Abstract: The aim of this study was to investigate the impact of signboard‐building color combinations on color harmony and legibility. Two hundred and three participants rated 54 signboard‐building color combinations against two scales of color harmony and legibility. In this article, the terms “brick,” “stone,” and “glass” refer to three types of building exteriors used in the experiment (ie, brick masonry, greystone, and curtain walls, respectively). Major findings are as follows: (a) there was a positive linear corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Some researchers have examined some of the aspects dealt with in this research. (Won, et al, 2020) studied the effect of colors and density on legibility. Regarding the effect of the number of signboard colors on color harmony, they did not include all factors and other variables of the signs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have examined some of the aspects dealt with in this research. (Won, et al, 2020) studied the effect of colors and density on legibility. Regarding the effect of the number of signboard colors on color harmony, they did not include all factors and other variables of the signs.…”
Section: Discussionmentioning
confidence: 99%
“…It includes variables and their characteristics according to previous studies. These variables were distributed according to their relationship to the four principles of livability as evaluated and reached by the researchers before (Jiuan, 1984;Abu-Ghazzeh, 1996;Morris, 2001;Hashim, 2001;Coetzee, 2003;Zineddin et al, 2005;Mulyaningsih, et al, 2012;SANTOSA et al, 2013;Wilsona et al, 2015;PESZKO, 2016;Wilson & Casper, 2016;Kim & Park, 2020;Laskara et al, 2020;Won & Lee, 2020;Y He, et al, 2020).…”
Section: Street Signsmentioning
confidence: 99%
“…Big data in the context of information technology has expanded the spatial and temporal dimensions of urban space, bringing an opportunity to refine urban planning and management, gradually moving from top-down control and adjustment of indicators to perceiving the city from the users' perspective, using open maps, streetscape images, virtual reality technology, and other means (Long and Tang, 2019). Won, Lee, and Park (Won et al, 2020) investigated the effect of colour combinations between shop signs and buildings on colour harmony and legibility; Zhong et al (Zhong et al, 2021) identified and extracted the dominant colours of urban buildings from street scene images and guided optimisation strategies. The study takes 'people' as the object of study, uses various measurement methods, uses 'subjective perceptions' as an intermediate medium and digitises them, uses statistics and analysis to investigate the correlation between the objective built environment and the subjective perceptions of users, and then translates the subjective perceptions into actionable aspects of the physical.…”
Section: Urban Cultural Landscape Identificationmentioning
confidence: 99%
“…Existing studies point out that in signage design, colors are more likely to achieve visual harmony when there is little chromaticity or a large difference in luminance [11]. Brightness differences have a stronger effect on harmony and legibility, while chromaticity has a lesser effect [15]. Different gender labels affect the degree of subjective preference for color and the response to the environment [16].…”
Section: Color Research In Public Facility Designmentioning
confidence: 99%